The other side of Guernica - Huerga Melcón, Pablo (Nómadas. Critical Journal of Social and Juridical Sciences, 2009)
The Picasso´s Picture, to what the press entitled “Guernica”, is the last manifestation of the classic mater of “adoration of the Shepherds”, which went from the medieval period, and integrates with the Spanish tradition of the “belenes”, and particularly with the andalusian tradition. In fact, the picture was more the motivation from the attack against Malaga in February of 1937, than Guernica in April of 1937. Our essay analyses not only the reason of the separate elements of the picture, but their articulation in a whole. A comprehensive interpretation of the whole elements makes evident that Picasso, the great iconoclast, is killing the picture of the adoration of the shepherds, in the same way that Spanish civil war is killing the civil population represented in the Sagrada Familia, in the same way that the Nazism is the God dead, the end of the values, the annunciation of the nihilism.